Efektivitas Pelatihan dan Pengembangan Dalam Meningkatkan Kualitas Sumber Daya Manusia di LKP Saraswati Ponorogo - Firza Ulynuha Amalia; Yulia Anggraini (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Along with the times, competition between organizations is getting tougher. As a competitor, every organization wants to be the best of other organizations. This situation will require every organization to measure the organization's operations or programs, known as effectiveness. Holding a training and development program is hoped to maintain and increase the effectiveness of the organization in achieving its goals. The purpose of this study was to analyze the effectiveness and impact of implementing training and development programs in improving the quality of human resources at LKP Saraswati Ponorogo. This study uses a type of field research with a qualitative approach. Data collection was done through interviews and observation. Data processing techniques are used by exposing, sorting, and drawing conclusions. Data analysis techniques include reduction, presentation, and conclusions. They are checking the validity of the data using triangulation techniques. The resource persons in this study were leaders from LKP Saraswati, administration, and training participants. The results of this study indicate that the implementation of training and development programs at the Saraswati Ponorogo Course and Training Institute to improve the quality of human resources has been quite effective. However, using time is less effective because some still need to finish their training period. The impact of the results of the implementation of this training and development program in terms of the knowledge of the participants has increased, and the abilities possessed by the participants have also increased, but there are still skills that could be improved.